2004
DOI: 10.1002/ange.200461801
|View full text |Cite
|
Sign up to set email alerts
|

Reductive N Alkylation of Cyclo[8]pyrroles

Abstract: Vier rauf, vier runter: Die reduktive Alkylierung von Cyclo[8]pyrrol und seinen Derivaten liefert die entsprechenden reduzierten per‐N‐alkylierten Produkte, eine Reaktion, die von Porphyrinen nicht bekannt ist. In diesen schalenförmigen Molekülen sind die acht Substituenten abwechselnd nach oben und nach unten gerichtet, wie die Kristallstrukturanalyse ergab (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[39] Remarkably, when [72a- 4 ] is subjected to a reductive alkylation reaction it yields products of the general structure 73a-R 8 (R = Me, Et, Bn), which show no significant absorption above 325 nm. [254] 73a-R 8 is formally a [32]annulenoid system but it largely behaves as a cyclic oligopyrrole with insignificant macrocyclic conjugation. In the solid state, 73a-Me 8 adopts an alternant "four up, four down" conformation with the N-alkyl groups located on both sides of the macrocycle ( Figure 14).…”
Section: T0 Systemsmentioning
confidence: 99%
“…[39] Remarkably, when [72a- 4 ] is subjected to a reductive alkylation reaction it yields products of the general structure 73a-R 8 (R = Me, Et, Bn), which show no significant absorption above 325 nm. [254] 73a-R 8 is formally a [32]annulenoid system but it largely behaves as a cyclic oligopyrrole with insignificant macrocyclic conjugation. In the solid state, 73a-Me 8 adopts an alternant "four up, four down" conformation with the N-alkyl groups located on both sides of the macrocycle ( Figure 14).…”
Section: T0 Systemsmentioning
confidence: 99%
“…1100 nm ( ε ≈130 000 mol −1 cm −1 ) 39. Remarkably, when [ 72a ‐H 8 ][SO 4 ] is subjected to a reductive alkylation reaction it yields products of the general structure 73a ‐R 8 (R=Me, Et, Bn), which show no significant absorption above 325 nm 254 . 73a ‐R 8 is formally a [32]annulenoid system but it largely behaves as a cyclic oligopyrrole with insignificant macrocyclic conjugation.…”
Section: Octaphyrinsmentioning
confidence: 99%
“…It was thus clear that in order to account for global effects, as well as to access different oxidation states, the imide group must be replaced by groups such as alkyl, which cannot participate in the resonance of the π‐conjugated backbone. However, since the high HOMO level of furan intermediates renders them unstable throughout the synthetic procedure, we found that a previous strategy applied to macrocyclic thiophenes and pyrroles, namely, the macrocyclization of β‐alkyl‐monomers, [35] is not applicable for furan analogs. We therefore postulated that the reduction of the imide group (which stabilize the intermediates) to amine should be performed post‐macrocyclization [36,37] …”
Section: Introductionmentioning
confidence: 97%